Respostas
respondido por:
1
Vamos lá ..
(x^2 - 2xy + y^2 - 2) + ( - x^2 + 2xy + y^2 + 2) = x^2 - x^2 - 2xy + 2xy + y^2 + y^2 - 2 + 2 = 2y^2
( x^3 - 3x^2 + 2x + 4) - (3x^2 + 5x^2 + x) = x^3 - 3x^2 - 3x^2 - 5x^2 + 2x - x + 4 = x^3 - 11x^2 + x + 4
Espero ter ajudado !!!
(x^2 - 2xy + y^2 - 2) + ( - x^2 + 2xy + y^2 + 2) = x^2 - x^2 - 2xy + 2xy + y^2 + y^2 - 2 + 2 = 2y^2
( x^3 - 3x^2 + 2x + 4) - (3x^2 + 5x^2 + x) = x^3 - 3x^2 - 3x^2 - 5x^2 + 2x - x + 4 = x^3 - 11x^2 + x + 4
Espero ter ajudado !!!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás